2006
DOI: 10.2174/138945006778559166
|View full text |Cite
|
Sign up to set email alerts
|

G-protein Dependent Platelet Signaling - Perspectives for Therapy

Abstract: Platelet activation and aggregation is an integral component of the pathophysiology that leads to thrombotic and ischemic diseases such as cerebral stroke, peripheral vascular disease and myocardial infarction. Anti-platelet agents (such as aspirin, ADP receptor antagonists, and GPIIb/IIIa antagonists), phosphodiesterase inhibitors and anti-coagulants are major part of the current treatment towards treating ischemic diseases. However, their limited efficacy in the setting of arterial thrombosis, unfavorable si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 148 publications
(192 reference statements)
0
20
0
1
Order By: Relevance
“…Moreover, it was reported that supplementing the diet with the antioxidants N -acetylcysteine and vitamin E markedly increases tumor progression and reduces survival in mouse models of B-RAF- and K-RAS-induced lung cancer, by reduction of ROS, DNA damage, and p53 expression (Sayin et al, 2014). On the contrary, the use of small molecules derived from diet that alter the levels of ROS, such as diallyl disulfide, polyphenols, isothiocyanates, and terpenoids has been suggested for the treatment of cancer by promoting ROS generation and GSH depletion in cancer cells (Filomeni et al, 2003; Shankar et al, 2006; Trachootham et al, 2006; Yue et al, 2006; Aquilano et al, 2010). Interestingly, depletion of mitochondrial GSH has also been associated with apoptosis or ATG induced by chemotherapeutic drugs (Samudio et al, 2005; Chen et al, 2011).…”
Section: Gsh Tips the Scales Between Survival And Cell Deathmentioning
confidence: 99%
“…Moreover, it was reported that supplementing the diet with the antioxidants N -acetylcysteine and vitamin E markedly increases tumor progression and reduces survival in mouse models of B-RAF- and K-RAS-induced lung cancer, by reduction of ROS, DNA damage, and p53 expression (Sayin et al, 2014). On the contrary, the use of small molecules derived from diet that alter the levels of ROS, such as diallyl disulfide, polyphenols, isothiocyanates, and terpenoids has been suggested for the treatment of cancer by promoting ROS generation and GSH depletion in cancer cells (Filomeni et al, 2003; Shankar et al, 2006; Trachootham et al, 2006; Yue et al, 2006; Aquilano et al, 2010). Interestingly, depletion of mitochondrial GSH has also been associated with apoptosis or ATG induced by chemotherapeutic drugs (Samudio et al, 2005; Chen et al, 2011).…”
Section: Gsh Tips the Scales Between Survival And Cell Deathmentioning
confidence: 99%
“…First, the protein is phosphorylated on tyrosine in response to GPVI ligation. Second, the phosphorylation event is critical for the physiological function of platelets (25)(26)(27)(28). Third, the protein should contain at least one Tyr(P) site that matches the substrate specificity profile of TULA-2 as revealed by the library screening and kinetic analysis.…”
Section: Tula2 Substrate Specificitymentioning
confidence: 99%
“…The importance of integrin a IIb b 3 in supporting the hemostatic function of platelets is underscored by the severe bleeding disorder suffered by individuals deficient in this receptor (termed Glanzmann's Thrombasthenia) (Nurden 2005(Nurden , 2006. The conversion of integrin a IIb b 3 to a fully activated state is critically dependent on the generation of one or more soluble agonists at the sites of vascular injury, including adenosine diphosphate (ADP), thromboxane A2 (TXA2), and thrombin (Gachet and Hechler 2005;Hirano 2007;Ruggeri 2002;Shankar et al 2006). Each of these agonists bind to specific G-protein coupled receptors (GPCRs) and stimulate platelet activation through well-defined signaling pathways (Fig.…”
Section: Basic Principles Of Platelet Adhesion and Activationmentioning
confidence: 99%